Experimental study of small-scale passive solar wall module with phase change material and Fresnel lens. (August 2018) - Mols, Toms; Dzene, Kristiana P.; Vanaga, Ruta; Freimanis, Ritvars; Blumberga, Andra
Abstract: The goal of this study is to assess latent and sensible energy accumulation in building envelope using PCM as heat accumulator and Fresnel lens as solar concentrator. Small-scale passive solar wall module with PCM and Fresnel lens was built and tested in laboratory. Results of the test module were compared to results obtained in the reference box with opaque wall insulated with mineral wool, and the same test module where PMMA acrylic glass was used instead of Fresnel lens. The test module with Fresnel lens compared to the reference wall generates very different behavior of both temperature and heat flux. Room temperature delay in the test module is 30 hours thus keeping the room warm for much longer time period by using accumulated solar energy. Results show that the test modules with Fresnel lens and PMMA acrylic glass shows almost the same results. Experimental study also shed light on the phase change process of paraffin as PCM.